1996
DOI: 10.1002/jlb.60.1.106
|View full text |Cite
|
Sign up to set email alerts
|

CD66a, CD66b, CD66c, and CD66d each Independently stimulate neutrophils

Abstract: Four members of the carcinoembryonic antigen family, CD66a, CD66b, CD66c, and CD66d, are expressed on human neutrophils. In neutrophils these proteins are activation antigens in that their surface expression is increased following stimulation. To examine their potential role in neutrophil signaling, the effects on neutrophil adhesion to human umbilical vein endothelial cells of a panel of well-characterized CD66 mAbs was tested. CD66a, CD66b, CD66c, and CD66d antibodies each increased neutrophil adhesion to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 23 publications
6
126
0
1
Order By: Relevance
“…34 CD66b is a glycoprotein believed to be involved in neutrophil activation and migration, by means of regulating the adhesive activity of CD11b/CD18. 35 L-selectin that is constitutively present on the neutrophil membrane is necessary for initial neutrophil-endothelial cell interaction that results in rolling of neutrophils on endothelium. 36 Activation of neutrophils by LPS causes shedding of L-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…34 CD66b is a glycoprotein believed to be involved in neutrophil activation and migration, by means of regulating the adhesive activity of CD11b/CD18. 35 L-selectin that is constitutively present on the neutrophil membrane is necessary for initial neutrophil-endothelial cell interaction that results in rolling of neutrophils on endothelium. 36 Activation of neutrophils by LPS causes shedding of L-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47]50 It has been suggested that the tyrosine kinase activity associated with CEACAM1 may play a role in signal transduction and cellular adhesion, and that CEACAM1 might affect many important regulatory functions, such as proliferation, apoptosis, differentiation, angiogenesis, immune responses, granulocyte activation and polarization of epithelial cells. 45,47,[51][52][53][54][55] Moreover, CEA-CAM1, like BCR/ABL, has been shown to associate with the actin cytoskeleton, possible by interacting with paxillin. [56][57][58][59][60] In the hematopoietic system no detailed studies on the expression of CEACAM1 in different cellular compartments are available, but during normal hematopoiesis the expression pattern of the CEACAM1, CEACAM6 and CEACAM8 molecules has been shown to change with different maturation stages, first appearing at the promyelocytic stage and then showing increased expression on myelocytes and metamyelocytes.…”
Section: Discussionmentioning
confidence: 99%
“…CD66b is a granulocyte activation marker. 20 The neutrophils were defined as cells with red cytoplasmatic staining and a segmented nucleus. Neutrophils were only evaluated in the intratumoral area.…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%